HUBUNGAN LINGKUNGAN KERJA DAN PERILAKU NELAYAN TERHADAP KEJADIAN PTERIGIUM DI DESA KEMANG KECAMATAN PANGKALAN KURAS KABUPATEN PELALAWAN - Novita Rany (STIKes Hang Tuah Pekanbaru, 2017)
Pterygium is a thickening of the conjunctiva or the white part of the eye on the side of the medial or lateral, usually in older people, but can also be found in young adults, and increasingly extends towards the cornea. Ultraviolet light is one factor that can increase the incidence of pterygium. This situation is an irritating phenomenon caused by ultraviolet light, drying and the environment with a lot of wind. Data from Kemang Postu found that 30 (80%) incidence of pterygium. The purpose of this research that determines the behavior of fishermen on the incidence pteirigum. This research is a quantitative research with cross sectional analytic design. This research was conducted in Desa Kemang District of Pangkalan Kuras Pelalawan June-July 2016, with a sampling technique in the study of saturated sampling. Data were collected using a questionnaire and profile data from Kemang Village office. Data analysis for bivariate with chi-square test on the degree of Î± = 0.05. The results showed that there is a relationship between knowledge p-value = 0.001 <0.05 POR = 18,083 (3.281-99.67), personal protective equipment fisherman p-value = 0.001 <0.05, POR = 14,000 (2.69-72.97) the role of power health with the results of p-value = 0.008 <0.05, POR 10,667 (1.92-59.20) and the period of 0,017 fishermen p-value <0.05, POR 7750 (1.53-39.12) with pterygium disease. Health workers should pay more attention to the fishing community in order to prevent and menangguangi incidence of pterygium.